2016
DOI: 10.14238/pi56.4.2016.215-20
|View full text |Cite
|
Sign up to set email alerts
|

Lactate clearance and mortality in pediatric sepsis

Abstract: Background Sepsis is a life-threatening condition often

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Similar to the present study, several authors postulated LacCl% to be higher in survivor children. 5,15,24 Others have found ΔLac to be an independent predictor of hospital mortality in adults 17,28 and postoperative serious adverse events in children. 29…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the present study, several authors postulated LacCl% to be higher in survivor children. 5,15,24 Others have found ΔLac to be an independent predictor of hospital mortality in adults 17,28 and postoperative serious adverse events in children. 29…”
Section: Discussionmentioning
confidence: 99%
“…14 LacCl% at the cutoff point of 30% to 34.7% resulted in greater sensitivity (75%-87.50%), specificity (96.5%-97%), PPV (90%-93.3%), and NPV (91.4%-93.3%) in other studies. 15,36…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies demonstrated that the ability to clear lactate to normal in patients suffering from septic shock was associated with an improved outcome, those authors coined the term "lactate clearance". 20 On the other hand, the value of albumin levels in predicting outcomes in inflammatory diseases is also well known. Artero et al 21 found that in patients with community-acquired blood stream infections, with severe sepsis or septic shock, hypoalbuminemia is the strongest predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%